Microteaching on pre-service teachers' education: literature review - Iliasova, Liliia; Nekrasova, Inna; Mena, Juanjo; Estrada-Molina, Odiel (Frontiers in Education, 2025)
Teaching is a complex profession that requires a balance of knowledge, pedagogical skills, and classroom management. As educators work to create engaging and inclusive learning environments, innovative approaches are needed to enhance teaching skills and support continuous professional development. Microteaching is a widely used training method that enables teachers to refine techniques, test strategies, and receive feedback in a controlled environment. This paper explores microteaching's concept, theoretical foundations, and practical implications for teacher training. Through a review of literature and empirical evidence from 2006 to 2023, the study highlights microteaching's benefits, challenges, and future directions, emphasizing its potential to transform teacher education and improve educational outcomes. A quantitative meta-analysis of studies from Web of Science and Scopus databases was conducted using the Prisma protocol and VoSViewer to synthesize findings and construct clusters, which actually differs our research from previous ones. The research concludes that microteaching is associated with positive outcomes in teacher education, helping aspiring teachers practice pedagogical skills effectively. The limitations of this review include selection bias, the focus on English-only studies, and the time period chosen. Further research is recommended to understand pre-service teachers' perspectives on microteaching and to empirically assess whether microteaching foundations enhance the student learning process and boost enthusiasm for their future profession.